Optimal higher education enrollment and productivity externalities in a two-sector model - Volker Meier; Ioana Cosmina Schiopu (Center for Economic Studies and ifo Institute (CESifo), 2012)
We investigate externalities in higher education enrollment over the course of development in a two-sector model. Each sector works with only one type of labor, skilled or unskilled, and individuals are differentiated according to their cost of acquiring human capital. Both sectors exhibit productivity externalities in the size of the skill-specific labor and in the average human capital of workers. When skill-biased technological change prevails, it may well be the case that intermediate stages of development witness underenrollment in higher education, while highly developed economies experience overenrollment.
Keywords: D62; H23; I21; J24; O10; 330; higher education; enrollment; externalities; two-sector model; Studium; Schulbesuch; Mehr-Sektoren-Modell; Produktivität; Humankapital; Externer Effekt; Theorie